Aplikasi Survey Kepuasan Pasien Terhadap Pelayanan Perawat Berbasis Mobile - Efendi, Yoyon; Swastikarini, Sunarti; Muzawi, Rometdo; Rizki, Alfi (STIKOM Tunas Bangsa Pematangsiantar, 2020)
RSD Madani is one of the referral hospitals owned by the Pekanbaru City Government. One form of public service is quality hospital services according to professional standards and service standards, which are the expectations of all hospital service users. However, the number of patient participation in filling out the questionnaire was still low compared to the number of patient visits. Not yet optimal survey on the implementation of patient satisfaction towards nursing services. This application displays five patient satisfaction survey questions and favorite nurses. This mobile application is connected to the google form and google sheet. The satisfaction survey shows emotional icons with five levels, such as very satisfied, moderately satisfied, less satisfied, and dissatisfied. The selection of favorite nurses was followed by 12 nurses in the inpatient unit. It is necessary to make a patient satisfaction survey application for mobile-based nursing services, especially in the inpatient unit of RSD Madani Pekanbaru. This application is used as a means of evaluation in assessing the performance of nurses in the hospital.